Prostitution as an act not subject to taxation in Polish law - Olczyk, Adam (Acta Universitatis Lodziensis. Folia Iuridica, 2017)
The aim of this publication is to bring closer legal regulations referring to the statement that prostitution does not constitute income subject to tax in Polish law. This notion has been frequently presented by administrative courts and tax authorities – and this issue is discussed in the first part of the article. The next one focuses on legal articles that regulate this tax exemption. In this unit the author also describes the individual tax interpretation published in a case of so-called virtual prostitution. Third part concerns a moral aspect of sex acts in exchange for payment as well as possible ways of argumentation in such cases. At the end the author presents practice of arrangements that the Polish tax authorities pursue to establish if a taxpayer really engages sexual relations for financial benefits (like distinction between prostitution and donation).